EMBODIED PEDAGOGY DALAM HADITS JIBRIL: ANALISIS HERMENEUTIKA TERHADAP RELASI GURU-MURID DI ERA DISRUPSI DIGITAL - Udi Taryudi; Taufiq Fauzan Ginanjar (Berajah Journal, 2025)
Write A This article aims to explore the concept of embodied pedagogy and teacher authority in the Hadith of Jibril as a response to the phenomenon of digital education disruption which tends to be disembodied (detached from physical interaction and values). This research fills a gap in the literature which has dominantly positioned the Hadith of Jibril within the theological realm. Using a qualitative approach with hermeneutic content analysis method, this study finds that the Jibril-Prophet interaction is not merely normative ethics, but a blueprint for knowledge transmission mechanisms requiring intellectual readiness and pedagogical intimacy (proxemics). The theoretical implications of this study offer a model for integrating tacit knowledge into the contemporary Islamic education curriculum.